The treatment of epilepsy - Shorvon, S. D. (Simon D.); Perucca, Emilio; Engel, Jerome, Jr. (Chichester, West Sussex, UK ; Hoboken, NJ : John Wiley & Sons Inc., 2016)
The Treatment of Epilepsy, fourth edition, is a comprehensive reference and clinical guide to the pharmacological, medical and surgical options available in the treatment of epilepsy. -The text is compiled by a group of internationally renowned editors and contributors and is now in full color and extensively illustrated -The first two sections cover the background to, and principles of, treatment in different clinical situations -Section three comprises a series of systematic reviews of contemporary drug therapy, devoting one chapter to each anti-epileptic drug and covering all clinically-relevant aspects -Section four focuses on the surgical options, devoting individual chapters to each of the modalities of presurgical assessment and to each surgical operation or approach -This 4th edition is extensively revised incorporating the many recent developments in therapy, and comprises 81 chapters from world experts from 18 countries.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Epilepsy -- drug therapy; Anticonvulsants -- therapeutic use; Epilepsy -- surgery; Epilepsy; Anticonvulsants -- Therapeutic use; Epilepsy -- Surgery; Epilepsy -- Chemotherapy; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Anticonvulsants -- Therapeutic use; Epilepsy; Epilepsy -- Chemotherapy; Epilepsy -- Surgery; Medical; Electronic books